Eating Disorders as Social Justice Issues: Results from a Focus Group of Content Experts Vigorously Flapping Our Wings - Russell-Mayhew, Shelly; Stewart, Marion; MacKenzie, Stephanie (Canadian Journal of Counselling and Psychotherapy, 2008)
Feminists have led the way in conceptualizing eating disorders as political issues and advocated for consideration of the larger socioeconomic context. Given the lack of research specific to the area of eating disorders and social justice, a focus group with professional women was conducted in an attempt to move beyond the conceptual contributions in the literature. Results indicate that the depth, breadth, complexity, and pervasiveness of the problems that contribute to starvation, including starvation from eating disorders, require a global perspective that may be informed by social justice. Feminist scholarship and chaos theory inform the discussion.